A INFLUÊNCIA DA APLICAÇÃO DE EXERCÍCIOS DE TRÍCEPS SOBRE A ESTIMULAÇÃO DO PEITORAL NO EXERCÍCIO SUPINO RETO - UM ESTUDO ELETROMIOGRÁFICO - Daiane da Rosa; Moacir Pereira Junior; Fabio Henrique Ornellas; Hildegard Hedwig Pohl (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
Objective: To investigate the difference electromyography registers of the pectorals major muscle in the bench press exercise with or without prior triceps fatigued. Materials and Methods: The study included four male subjects aged 22-25 years with intermediate level training in bodybuilding, with goals in muscle hypertrophy, without any infirmity presented. The subjects performed 10 maximal repetitions in bench for electromyography evaluation. The procedure used for the analysis was the gathering of the electromyography signal of the pectorals major during movement execution of the bench press exercise without the exercises for triceps and their implementation on different days, with 80 hours apart. Results: It was found that changes were found in the electromyography signal in bench press exercise when compared with the burden versus performing triceps exercises before the bench press exercise. Conclusion: Thus differences were found when relating the load imposed on the bench press exercise to perform the same on the stimulation of the pectorals major, whether this is done before or after exercise for the triceps.